Influence of the estimated glomerular filtration rate equation on carboplatin dosing: a real-world study - Fortunato, Ana Rita; Barbosa, Cátia; Araujo, Ariana; Fernandez-Llimos, Fernando (Frontiers in Pharmacology, 2025)
BackgroundCarboplatin is a renally excreted antineoplastic drug associated with myelotoxic effects. Doses are calculated according to the Calvert formula. The change from Cockcroft-Gault (CG) to the race-free Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) may have an impact on doses. The aim of the study was to evaluate the difference in carboplatin doses based on estimated glomerular filtration rate (eGFR) calculated using the two different equations (i.e., CG and CKD-EPI) applied to a real-world dataset of carboplatin administrations.Materials and methodsRetrospective study simulating the effect of switching to CKD-EPI on doses calculated using CG. Real-world data were collected on all carboplatin doses administered in a general hospital oncology day-care unit during 2023. Doses originally calculated using CG estimates were recalculated using CKD-EPI results. A Bland-Altman analysis was performed to assess the discrepancies between the two equations. Correlations with anthropometric data were examined.ResultA total of 487 cycles were administered to 126 patients with a mean age of 58.3 years (SD 12.6), 60.3% were female. There was a significant mean difference (p < 0.001) with a moderate effect (Cohen’s d = 0.474) between clearance calculated with CG and eGFR calculated with CKD-EPI. CKD-EPI calculated doses had a mean 52 mg higher (limits of agreement −107 + 211). Percentage differences between CKD-EPI and CG doses ranged from +70.9% (CG = 405 mg, CKD-EPI = 692 mg) to −24.3% (CG = 684 mg, CKD-EPI = 518 mg). Differences were strongly correlated with body mass index (BMI) (p < 0.001, R = 0.681).ConclusionClinically relevant differences were found between carboplatin doses calculated with CG and CKD-EPI. These differences were more relevant in male patients with low BMI.